Regular integral models for Shimura varieties of orthogonal type. Issue 4 (15th April 2022) - Pappas, G.; Zachos, I.
Abstract : We consider Shimura varieties for orthogonal or spin groups acting on hermitian symmetric domains of type IV. We give regular $p$ -adic integral models for these varieties over odd primes $p$ at which the level subgroup is the connected stabilizer of a vertex lattice in the orthogonal space. Our construction is obtained by combining results of Kisin and the first author with an explicit presentation and resolution of a corresponding local model.